Cervical cancer screening in rural South Africa among HIV-infected migrant farm workers and sex workers - Omara Afzal; Molly Lieber; Peter Dottino; Ann Marie Beddoe (Elsevier, 2017)
At an HIV clinic in the Limpopo province of South Africa, chart reviews revealed long delays in addressing abnormal Pap smears, difficulty in referrals, poor quality and lost results, and increasing cases of cervical cancer. To address these barriers, a "see and treat" approach to screening was proposed. The objective was to integrate this method into current HIV care offered by local providers and to obtain demographic and risk factor data for use in future educational and intervention programs in the region. A cross sectional study of HIV farm workers and at-risk sex workers attending an HIV clinic was performed with visual inspection with acetic acid (VIA). Those with positive screens were offered cryotherapy. Clinic charts were reviewed retrospectively for Pap smear results for the previous year at the time of program initiation and at 12 and 18 months post-program. A total of 403 participants consented and underwent screening with VIA (306 Farm workers and 97 sex workers participated). 83.9% of participants (32.9% sex workers and 100% farm workers) were HIV+. VIA was positive in 30.5% of participants, necessitating cryotherapy. There was no significant difference in VIA positivity between HIV+ farm workers and sex workers. There was a positive correlation between Pap smears and VIAs results. We demonstrate successful integration of cervical cancer screening using VIA for HIV+ farm workers and sex workers into an existing HIV treatment and prevention clinic in rural South Africa, addressing and treating abnormal results promptly.